Hegemony and alternatives in education policies for children in Colombia: subjects, discourses and practices (1982 - 2015) (2017)
It was studied from the interpretive history, the meaning; sense; transformations and scope of education policy for children. This paper reveals how the education reforms promoted since the enactment of the Political Constitution of 1991, the General Education Law (115/94) and the Children's Code (1098/2006) constitute discourses shaped by tensions between the hegemonic proposals and alternative constructions led by different social and political groups. These tensions, over time, show that the educational transformations sink their roots in alternative proposals that address both the hegemonic approaches and the educational reality of the country. The study is part of a historical vision that recovers different aspects of humanity such as culture, meanings, subjects, knowledge, practices and discourses; all these, elements that can be resignified and become meaningful to the extent that they can be assumed as a source of information.This research used the qualitative documentary methodology focused on the discursive production of education policy, pedagogy, and education in established periods. These discourses made up the documentary archive where it was possible to unveil the intentions, senses and meanings of those who produced them. Transformations and contributions achieved in the field of children's education, during this period, are explained.